DESIGN OF LOW DRAG REACTIVE SILENCERS BASED ON THE BOUND STATES IN THE CONTINUUM - Hruška, Viktor; Krpenský, Antonín; Bednařík, Michal; Czwielong, Felix (Proceedings of Forum Acusticum, 2023)
The phenomenon of bound states in the continuum and leaky resonances is employed to design a reactive silencer. It is targeted to prevent a significant spectral line from propagating in a flow-duct while maintaining low pressure drop and installation space (without any lateral extensions). The quasi bound states are achieved by tuning the geometrical parameters of thin plates embedded in a waveguide with dimensions and flow velocities typical for ventilation systems. In general, the procedure works for waveguides with plane wave propagation in the low Mach number regime. An optimization by evolution strategies used for this purpose is described and illustrated on two specific examples.
CRIS-Team Scopus Importer:2024-12-16
Keywords: bound states in the continuum; flow ducts; numerical optimization; reactive silencer